EFFECTIVENESS OF THERAPEUTIC ULTRASOUND IN THE TREATMENT OF PLANTAR FASCIITIS: A SYSTEMATIC REVIEW (The Research of Medical Science Review, 2025)
Background: Plantar fasciitis is a common cause of heel pain, often managed conservatively with therapeutic ultrasound (US), though its effectiveness remains unclear.Objective: To evaluate the effectiveness of therapeutic US in reducing pain and improving function in plantar fasciitis.Methods: A systematic review of randomized controlled trials (RCTs) was conducted. Studies comparing US with placebo, no treatment, or alternatives (e.g., rESWT, dry needling) were included. Outcomes assessed included pain (VAS), function (FFI, AOFAS), mobility (PFPS), and satisfaction. Risk of bias was evaluated using the Cochrane RoB 1 tool.Results: Eight RCTs (418 participants) were included. Most showed significant pain reduction and functional improvement with US, especially when combined with exercise. However, US was generally less effective than rESWT. Risk of bias was moderate to high due to methodological limitations.Conclusion: Therapeutic ultrasound may modestly improve pain and function in plantar fasciitis, particularly alongside exercise, but appears less effective than shockwave therapy. More rigorous, long-term studies are needed.